Kualifikasi dan Kompetensi Pendidik di SD N 25 Lubuk Lintah - Intan Sara (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
Quality education relies on educators who meet specific qualifications, including formal education and certification. The qualifications of educators are regulated by Law No. 14 of 2005 and the Minister of National Education Regulation, emphasizing the necessity of pedagogical, personal, and professional competencies. Observational results indicate that the majority of teachers at SDN 25 have met the established qualifications, with several teachers already certified. This reflects a commitment to improving teaching quality and positively impacting students. With adequate qualifications, educators are better prepared to face the evolving challenges of education, thereby providing quality and relevant education for future generations.